Value addtion of locally adapted underutilized crops - Sharma, Neetu; Dogra, Vishal; Kumar, Deep (Indian Farming, 2018)
The result concludes theadvantages offered by theunderutilized and neglected crops inenhancing the nutritional security oflocal communities and enhancingtheir income though this valueaddition venture. The uniquestrength of certain underutilized andneglected crops in their rich andfavourable nutritional compositionand product development offersuncommon opportunities for incomegeneration to the farmers, inparticular the farm-women.